EXPLORING RELIGIOUS MODERATION: A Washatiyyah Perspective in Tafsir Tahlili Al-Qur'an - Achmadin, Balya Ziaulhaq; Fattah, Abdul; Mukhsin, Akhmad; K. Amrullah, Abdul Malik; Barizi, Ahmad (Muta'allim: Jurnal Pendidikan Agama Islam, 2025)
This study aims to analyze the construction of Washatiyyah (moderation) in a religious context based on the perspective of the Quran, with a focus on of the study of Tahlili interpretations of the Qur'an. The method of qualitative analysis is used with a descriptive approach, involving the search of the literature, the collection of data from the relevant Tahlili interpretations, as well as the analysis and interpretation from the verses of the Koran related to religious moderation. The study is aimed at providing a deeper understanding of the constructions of religious Washatiyya in a Koran perspective, with practical implications in guiding Muslims in practicing religious moderation and building inclusive, tolerant, and harmonious societies. The study also aims to reveal the understanding and interpretation of scholarship related to religious moderation, such as the principles, values, and examples of the verses of the Qur'an that describe moderate attitudes in religion. Using the Qur'anic interpretation as a primary source, the study seeks to provide practical guidance for Muslims in applying religious moderation in everyday life. The findings of this research are expected to make an important contribution to developing thought and understanding of religious moderation from the perspective of the Qur'an, as well as promoting social peace and interreligious congregation. In the context of building inclusive and harmonious societies, a deeper understanding of religious Washatiyyah construction will be a strong foundation for overcoming conflict and enhancing tolerance in religious life.AbstrakPenelitian ini bertujuan untuk menganalisis konstruksi Washatiyyah (moderasi) dalam konteks keagamaan berdasarkan perspektif Alquran, dengan fokus kajian pada tafsir-tafsir Tahlili Alquran. Metode yang digunakan adalah metode analisis kualitatif dengan pendekatan deskriptif, yang melibatkan penelusuran literatur, pengumpulan data dari tafsir-tafsir tahlili yang relevan, serta analisis dan interpretasi dari ayat-ayat al-Qur'an yang berkaitan dengan moderasi beragama. Penelitian ini bertujuan untuk memberikan pemahaman yang lebih mendalam tentang konstruksi keagamaan Washatiyyah dalam perspektif Alquran, yang berimplikasi praktis dalam memandu umat Islam dalam mempraktikkan moderasi beragama dan membangun masyarakat yang inklusif, toleran, dan harmonis. Penelitian ini juga bertujuan untuk mengungkap pemahaman dan penafsiran para ulama terkait dengan moderasi beragama, seperti prinsip-prinsip, nilai-nilai, dan contoh-contoh ayat-ayat al-Qur'an yang menggambarkan sikap moderat dalam beragama. Dengan menggunakan tafsir Al-Qur'an sebagai sumber utama, penelitian ini berusaha memberikan panduan praktis bagi umat Islam dalam menerapkan moderasi beragama dalam kehidupan sehari-hari. Temuan penelitian ini diharapkan dapat memberikan kontribusi penting dalam mengembangkan pemikiran dan pemahaman tentang moderasi beragama dalam perspektif Al-Qur'an, serta mempromosikan perdamaian sosial dan kerukunan antarumat beragama. Dalam konteks membangun masyarakat yang inklusif dan harmonis, pemahaman yang lebih mendalam tentang konstruksi keagamaan Washatiyyah akan menjadi fondasi yang kuat untuk mengatasi konflik dan meningkatkan toleransi dalam kehidupan beragama.